METODE DIAGNOSIS INFEKSI TRICHOMONAS VAGINALIS TERKINI - Tambunan, Ronald T. H. (Universitas Methodist Indonesia, 2024)
Recent advances in tests for the sexually transmitted protozoan parasite Trichomonas vaginalis have increased opportunities for diagnosis and treatment of this important sexually transmitted infection. This review summarizes current available tests, highlighting their performance characteristics, advantages, and limitations. The recent development of molecular tests for the detection of T vaginalis, including rapid antigen detection and nucleic acid amplification tests, has significantly improved the quality of diagnostics for trichomoniasis, particularly in women. In light of the expanded menu of testing options now available, improved recognition and better control of trichomoniasis are in sight, which should enable the eventual reduction of adverse reproductive consequences associated with T vaginalis infection.